Comment on Hladky-Krage, B.; Hoffman, C.L. Expectations versus Reality of Designer Dog Ownership in the United States. Animals 2022, 12, 3247 - Amanda J. Venturino; Katie M. Weaver; Cornelia Kraus; Jessica P. Hekman (Animals)
Designer dogs—the result of intentionally crossbreeding purebred dogs, and specifically poodle mixes (a cross between a poodle and a second breed)—have rapidly grown in popularity in recent years [...]